云油茶良种在贵州低热河谷区引种表现评价Evaluation on the introduction and cultivation of Yunnan Camellia oleifera superior varieties in low thermal valley area of Guizhou - 张健1，郭广正2，徐德兵3，康专苗2，王代谷2，梁永顺1 ZHANG Jian1, GUO Guangzheng2, XU Debing3，KANG Zhuanmiao2, WANG Daigu2, LIANG Yongshun1 (Zhongguo youzhi)
为明确云油茶系列良种在贵州低热河谷区的引种栽培适应性，基于果实、种子、产量及油脂品质等性状指标对云油茶3号、云油茶4号、云油茶9号、云油茶13号和云油茶14号5个良种在贵州低热河谷区的栽培表现进行分析和评价。结果表明：5个云油茶品种果实性状中，单果质量最大的是云油茶14号，果实均匀度最好的为云油茶9号，果皮厚度最小的是云油茶13号，果形最圆的为云油茶9号和云油茶13号，鲜果出籽率和干出籽率最大的均为云油茶13号；5个云油茶品种种子性状中，单籽质量最大的是云油茶9号，种子均匀度最好的为云油茶3号，干籽出仁率、种子含水率和种仁脂肪含量最高的分别是云油茶13号、云油茶9号和云油茶4号；5个云油茶品种产量和油脂品质性状中，云油茶3号的3年平均结果量最高，为3.59 kg/株，云油茶13号的果油率最高，5个云油茶品种油脂不饱和脂肪酸含量均在90%以上，饱和脂肪酸、不饱和脂肪酸、单不饱和脂肪酸含量最高的分别是云油茶9号、云油茶14号和云油茶4号。相关性分析表明：云油茶果实、种子、产量性状指标之间存在较强的相关性。通过主成分分析得到5个云油茶品种的引种表现综合评价高低排序为云油茶13号、云油茶4号、云油茶3号、云油茶14号和云油茶9号。综上，可优先推荐云油茶13号、云油茶4号和云油茶3号在贵州低热河谷区进行推广种植，以丰富贵州低热河谷区油茶品种结构。To clarify the adaptability of the Yunnan Camellia oleifera series of superior varieties in low thermal valley area of Guizhou for introduction and cultivation，the cultivation performances of five Yunnan Camellia oleifera superior varieties, namely No.3, No.4, No.9, No.13, and No.14, in low thermal valley area of Guizhou were analyzed and evaluated based on the trait indicators such as fruits, seeds, yields and oil quality. The results indicated that regarding fruit traits, the fruit with the largest mass was No.14, the one with the best fruit uniformity was No.9, the one with the thinnest pericarp was No.13, the one with the roundest fruit was No.13 and No.9, and the rates of seed extraction from fresh fruits and dry fruits were both the highest for No.13. In terms of seed traits, No.9 had the highest seed mass, No.3 had the best seed uniformity, No.13, No.9 and No.4 had the highest kernel yield of dry seed, seed moisture content and seed kernel fat content, respectively. In terms of fruit yield and oil quality, the 3-year average fruit yield of No.3 was the highest at 3.59 kg per plant, No.13 had the highest fruit oil content, and the five Yunnan Camellia oleifera varieties all had more than 90% unsaturated fatty acids. No.9, No.14 and No.4 had the highest content of saturated fatty acids, unsaturated fatty acids and monounsaturated fatty acids, respectively. Correlation analysis demonstrated a strong correlation among the trait indicators of fruits, seeds and yields. The ranking of the introduction performance evaluation for the five Yunnan Camellia oleifera varieties obtained through principal component analysis was as follows: No.13, No.4, No.3, No.14 and No.9. In conclusion,it is recommended to prioritize the promotion and cultivation of No.13, No.4 and No.3 in low thermal valley area of Guizhou to enrich the variety structure of Camellia oleifera in this region.